[OP.4A.03] PUBLIC HEALTH IMPACT OF CARDIOVASCULAR TREATMENTS IN PRIMARY PREVENTION: A SIMULATION STUDY ON A VIRTUAL REALISTIC POPULATION. (September 2017) - Fall, M.; Le, H.; Marchant, I.; Gueyffier, F.
Abstract : Objective: Cardiovascular disease is responsible for about one third of cardiovascular death worldwide and is the first cause of morbidity-mortality in France. Patients in primary prevention present important risk of cardiovascular disease. Predicting public health impact of cardiovascular treatments in primary prevention to better optimize them in this population is a major challenge. Four main classes of drugs used in primary prevention include blood lowering, cholesterol lowering agents, aspirin and anti-diabetic agents. We aimed to assess the efficacy of monotherapy or combined therapies of these drugs in primary prevention on a virtual realistic population (VRP) in function of their predicted cardiovascular risks. Design and method: A French VRP was generated using the most available representative data from related French cohorts (eg. MONICA-France study). Cardiovascular death risk of each virtual patient was calculated by applying SCORE. The VRP was then divided in six categories in function of gender and individual risks of cardiovascular death: low risk (<1%), intermediate risk (1–5%) and high risk (>5%). We estimated reduced risk by each treatment using their relative risks obtained from most related powerful meta-analyses or trials. Therapy efficacy was examined in terms of reduced risks and number needed to treat (NNT). Results: 1 062 874 virtual patients were generated in a French VRP in primary prevention with 14 variates: age, sex, weight, height, smoking status, glucose level, systolic/diastolic blood pressure, baseline type 2 diabetes, baseline left ventricular hypertrophy, creatinine, total cholesterol, HDL and LDL. In our simulation, the tritherapy (aspirin, statin and anti-hypertensive agent) seemed to bring the most beneficial effect for primary prevention patients (Fig. 1). Figure. No caption available. Conclusions: Our approach allows estimating the public health impact of several cardiovascular treatments in primary prevention, further optimizing therapeutic strategies in function of patient particularities (gender, cardiovascular risks) and illustrating a perspective towards a better personalize medicine.